Islamic finance and sustainable development - Hassan, M. Kabir 1963-; Aishath Muneeza 1983-; Rashedul Hasan 1987- (Cambridge elements. Elements in economics of emerging markets, 2025)
Islamic finance is rooted in Shariah or Islamic law, which promotes the well-being of humanity and discourages harmful practices. This Element highlights the nexus between Islamic finance and sustainable development, emphasizing the ethical and socially responsible nature of Islamic finance. It discusses how Islamic financial institutions contribute to sustainable development through the achievement of Sustainable Development Goals , Environmental, Social, and Governance criteria, and Socially Responsible Investment practices. Case studies from different parts of the world demonstrate practical applications of Islamic finance principles in supporting SDG. It suggests reforms that can unlock the full potential of Islamic finance, including the institutionalization of Islamic social finance, convergence with commercial finance, leveraging technology, integrating Shariah-based financial products, considering social return as a benchmark for approving products, introducing blended finance, and collaborating with humanitarian agencies. The potential of Islamic finance for sustainable development provides valuable insights for academicians, practitioners, and policymakers